Determination of surface and interface magnetic properties for the multiferroic heterostructure Co/BaTiO3 using spleed and arpes. (7th September 2016) - Borek, St; Braun, J; Minár, J; Kutnyakhov, D; Elmers, H-J; Schönhense, G; Ebert, H
Abstract: Co/BaTiO3 (0 0 1) is one of the most interesting multiferroic heterostructures as it combines different ferroic phases, setting this way the fundamentals for innovative technical applications. Various theoretical approaches have been applied to investigate the electronic and magnetic properties of Co/BaTiO3 (0 0 1). Here we determine the magnetic properties of 3 ML Co/BaTiO3 by calculating spin-polarized electron diffraction as well as angle-resolved photoemission spectra, with both methods being well established as surface sensitive techniques. Furthermore, we discuss the impact of altering the BaTiO3 polarization on the spectra and ascribe the observed changes to characteristic details of the electronic structure.